PELAKSANAAN PEMBEBASAN BERSYARAT BAGI WARGA BINAAN DALAM UPAYA RESOSIALISASI DI LEMBAGA PEMASYARAKATAN KELAS II A DENPASAR - Haidi Partogi, Marbui; Surya Darmajaya, Ida Bagus; Walesa Putra, I Made (Kertha Wicara : Journal Ilmu Hukum, 2015)
Correctional system is held in order to establish prisoners to be fully human, awareof the error, improve themselves, and not repeat the criminal offense that can be acceptedby society, can actively participate in the development, can live reasonably as good citizensand responsible . Inside the prison inmates are entitled to a reduction in future criminal orremission, Assimilation, Leave Visiting Family and Parole and leave Toward Free. Thepurpose of this study is to describe the implementation of parole and things that hinder theimplementation of parole in an effort resocialization. The type of research used theempirical research. Implementation parole descriptively according to the Regulation of theMinister of Law and Human Rights No. 21 Year 2013 on Terms and Procedures for theImplementation of Assimilation, parole, leave Towards Free, and leave Conditional. In theimplementation of parole are the barriers like not having a guarantor, disciplinary offenses,the lack of correctional employees, and given the lack of adequate budget.
Keywords: Lembaga Pemasyarakatan, Pembebasan Bersyarat, Warga Binaan, Resosialisasi